Evaluation of the Antibiotic Resistance Rate of Helicobacter pylori in Peptic Ulcer Patients in Tien Giang Central General Hospital, Tien Giang Province, Vietnam - Nhu, Le Tran Thi; Nguyen, Van Lam; Tran, Van De; Tran, Ngoc Anh; Nguyen, Vu Trung (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Peptic ulcer (PU), trauma on the lining of the stomach and/or small intestine, is among the top five reasons for hospitalization in Tien Giang, a province in the South of Vietnam. Since Helicobacter pylori (HP) is one of the main causes of PU, its features, especially the antibiotic-resistant status, have critical significance in PU treatment. AIM: This study evaluates the HP infection prevalence, HP antibiotic resistance rate, and its associations with the patients’ sociodemographic characteristics. MATERIALS AND METHODS: A cross-sectional study was conducted on PU patients in Tien Giang province, Vietnam, from June 2020 to June 2021. The volunteers were tested for HP infection and antibiotic resistance using three methods, where appropriate, including Gram staining, CLO (urease) test, and bacterial culture method. RESULTS: Among 368 samples, 31.5% had infected with antibiotic-resistant HP. The resistance rates to five antibiotics commonly used in HP treatment, including metronidazole, clarithromycin, tetracycline, levofloxacin, and amoxicillin, were 96.6%, 94.8%, 70.7%, 61.2%, and 53.4%, respectively. The rates of tetracycline and clarithromycin resistance were related to alcohol consumption (t-test, p < 0.05). The HP treatment history was significantly associated with the levofloxacin resistance (t-test, p < 0.05). CONCLUSIONS: The emergence of antibiotic-resistant HP is a major public health concern in Tien Giang, Vietnam. This issue should be tackled at the national level to avoid the further spread of these multi-drug resistant HP strains.